Predictive Value of IL-6 and Lymphocyte Subsets for Death in Children With Influenza-Associated Encephalopathy A Retrospective Study - Ruiyang Sun; Xue Zhang; Jiapu Hou; Wanyu Jia; Peng Li; Daobin Wang; Shuqin Fu; Chunlan Song (Mediators of Inflammation)
Conclusion: The IL-6 concentration, percentage of CD4+ T cells, percentage of NK cells, and CD4+/CD8+ have predictive value for death in children with IAE, and the combination of these four metrics has improved the predictive value.